The sovereign remedy? trade agreements in a globalizing world - Estevadeordal, Antoni; Suominen, Kati. (Oxford : Oxford University Press, 2009)
Drawing on a number of unique new datasets, the authors seek to explore, in historical context, the relationship between trade agreements and the flow of global trade, and to identify how governments and countries might unilaterally and collectively leverage trade agreements to increase trade and prosperity.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International trade; Commercial treaties